2022
DOI: 10.1038/s41598-022-10985-4
|View full text |Cite
|
Sign up to set email alerts
|

Backward and forward neck tilt affects perceptual bias when interpreting ambiguous figures

Abstract: The relationships between posture and perception have already been investigated in several studies. However, it is still unclear how perceptual bias and experiential contexts of human perception affect observers’ perception when posture is changed. In this study, we hypothesized that a change in the perceptual probability caused by perceptual bias also depends on posture. In order to verify this hypothesis, we used the Necker cube with two types of appearance, from above and below, although the input is consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In those instances, eye movements help to disambiguate the percept ( Naji and Freeman 2004 ); instead of inducing ambiguous interpretations. Accordingly, eye movements are not the only actions that should be considered during bistability, but also head movements, as it has been shown that the position of the neck affects bistability ( Sato et al. 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In those instances, eye movements help to disambiguate the percept ( Naji and Freeman 2004 ); instead of inducing ambiguous interpretations. Accordingly, eye movements are not the only actions that should be considered during bistability, but also head movements, as it has been shown that the position of the neck affects bistability ( Sato et al. 2022 ).…”
Section: Discussionmentioning
confidence: 99%